Mitigating public speaking anxiety among EFL learners through peer teaching: An evaluative survey study - Ayiz, Abdul; Tauchid, Ahmad (CV. Yudhistt Fateeh, 2024)
This study investigates the effectiveness of peer teaching in reducing public speaking anxiety among English as a Foreign Language (EFL) learners. Public speaking anxiety is a prevalent issue among EFL learners, hindering their language development and performance. This research employs an evaluative survey design to assess the impact of peer teaching on public speaking anxiety among 67 EFL students. The results show a statistically significant reduction in public speaking anxiety after participating in peer teaching sessions, with a mean anxiety score decreasing from 64.23 to 54.44. The qualitative data further supports the quantitative findings, indicating that peer teaching fosters a collaborative learning environment, reduces fear of judgment, and provides constructive feedback, leading to increased confidence and reduced anxiety. The study highlights the pedagogical value of peer teaching in EFL classrooms, suggesting that it can be a useful tool in addressing public speaking anxiety and improving language learning outcomes.